Analysis of Price and Product Quality on Impulsive Buying on Online Shopping Platforms: Islamic Economic Approach - Nurhidayatullah; Navirta Ayu; Susiana Herawati (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2025)
Advancements in the field of communication and information technology have an impact on the economic sector. This is evidenced by the increasing number of online shopping centers offering a variety of products. As the number of online stores grows, it encourages society to shop freely. The decision to make a purchase lies with the consumer, who will determine the criteria for purchasing a particular product. Consumers will naturally choose products that are of good quality and offered at a lower price. Consumption behavior is no longer about fulfilling needs but merely about satisfying desires. Consumptive behavior in society, where goods or products are purchased without careful consideration and are driven solely by emotional impulses (desires), is known as impulsive buying. Therefore, the aim of this research is to explain how the price and quality of products influence impulsive buying behavior in online shopping and how Islamic economics views impulsive buying behavior. A quantitative research design was used as the main method, with a sample of 80 respondents from Kalurahan Gombang, internet users, specifically those who have made online transactions or shopping. Based on the data analysis results, it was found that the variables of price and product quality have an influence on impulsive buying in online shopping, and Islamic economics views impulsive behavior as prohibited because it is considered wasteful.